Saddlery and dyeing in the Sierra de Ancasti, Catamarca, Argentina - Martínez, Gustavo Javier (Ethnobotany Research and Applications, 2020)
Resumen Antecedentes: Las plantas curtientes y tintóreas han concitado el interés de diferentes investigaciones en la temática vinculada a la talabartería y la tejeduría tradicional, dos formas tradicionales de labor en creciente desuso. El objetivo de este trabajo es documentar la etnobotánica relacionada con especies tintóreas y curtientes de la sierra de Ancasti, Catamarca, Argentina. Métodos: Se seleccionaron 46 unidades domésticas a las que se aplicaron encuestas etnobotánicas generales; de manera particular fueron escogidos intencionalmente según la experticia cuatro informantes claves que, de acuerdo a su oficio aportaron información específica y en profundidad sobre talabartería, tejeduría y tinturas. Se trabajó con las fases del trabajo etnobotánico: trabajo de campo y de laboratorio, recolectando e identificando especies vegetales curtientes tintóreas y de interés en cultura material. Resultados: Un total de 34 especies pertenecientes a 22 familias botánicas comprenden el ámbito de la cultura material, curtiente y tintórea, siendo la familia Fabaceae la más representada (7 spp.). En general nuestras observaciones dieron cuenta del empleo de bastidores y marcos. Menos frecuente es el empleo del telar criollo. La preparación de la tinción es un proceso que involucra a toda la familia siendo una labor considerada localmente como femenina. Conclusiones: La práctica del teñido natural está todavía vigente en Ancasti y constituye una actividad promisoria. La actividad tintórea y de talabartería se encuentra en el conocimiento y manos de pocos pobladores por lo que sería deseable se desarrollen instancias participativas en las que se puedan compartir y hacer circular estos saberes locales. Palabras claves: plantas curitentes, tejeduría, tintes, Noroeste Argentino Extended Abstract Background: Tanning and dyeing plants have attracted the interest of different researches on the subject related to saddlery and traditional weaving, two traditional forms of labor in increasing disuse. The objective of this work is to document the ethnobotany related to dyeing and tanning species from the Sierra de Ancasti, Catamarca, Argentina. The specifics aims are to characterize relevant aspects of Creole saddlery, to characterize relevant species in the material culture associated with equestrian implements and to make a list of dyeing and tanning species used by the “criollo” peasant population Methods: The Ancasti mountain range is located in the east of the province of Catamarca and is considered an area of great biodiversity where the following ecoregions converge: Yungas (Selva de Transición, Selva Montana) [Yungas]; Monte de Sierras y Bolsones [Argentine Northwest Monte]; and Chaco Seco (Chaco Serrano) [Dry Chaco]. The community defines itself as “Criollos-serranos” and its subsistence economy is associated with traditional livestock production systems (cattle, goats, and sheep) and small-scale agriculture, mainly maíz (corn) (Zea mays L.) and zapallo (squash) (Cucurbita maxima Duch.). Forty-six household units were selected to which general ethnobotanical surveys were applied; in particular four key informants were intentionally chosen according to their expertise and their profession, provided specific and in-depth information on saddlery, weaving and dyeing. We worked with the phases of ethnobotanical work: field and laboratory work, collecting and identifying dye tanning plant species of interest in material culture. Results: A total of 34 species belonging to 22 botanical families comprise the material, tanning and dyeing culture, with the Fabaceae family being the most represented (7 spp.). In general, our observations showed the use of racks (for overcoat) and frames (for making rugs) and for the manufacture of other small pieces such as belts, peleros and caronillas. Less frequent is the use of the Creole loom. Staining preparation is a process that involves the entire family despite being a rather feminine task. Conclusions: The practice of natural dyeing is still in force at Ancasti and is a promising activity. However, dyeing and saddlery activities are in the knowledge and hands of few residents, so it would be desirable to develop participatory instances in which this local knowledge can be shared and circulated. Keywords: tanning plants, weaving, dyes, Argentine Northwest